2020
DOI: 10.3390/ijerph17051464
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Barriers and Facilitators of Maternal Health Care Utilization in Central Myanmar

Abstract: The study objective was to examine barriers and facilitators of maternal health services utilization in Myanmar with the highest maternal mortality ratio in Southeast Asia. Data for 258 mothers with children under five were extracted from a community health survey administered between 2016 and 2017 in Mandalay, the largest city in central Myanmar, and analyzed for associations between determinants of maternal health care choices and related outcomes. The study showed that late antenatal care was underutilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
4
28
0
3
Order By: Relevance
“…Findings from the study reveal that 181 (78%) supports the notion that transportation plays a huge role in the reduction of maternal mortality in Calabar; 148 (67%) agreed that good road network has an indirect role in reducing maternal mortality in Calabar; 146 (67%) opined that controlled traffic helps reduced maternal mortality in Calabar; 140 (64%) agreed that emergency vehicles such as ambulances are a good transport medium that reduces maternal death and 159 (71%) agreed that lack of access to transport for women in labour can increase stillbirth and maternal death rates. This study supports Milkowska-Shibata et al (2020). In their study, they identified barriers to accessing healthcare facilities to include transportation, health infrastructure in the rural areas.…”
Section: Hindrances To Access To Hospital Infrastructure In the Provisupporting
confidence: 58%
“…Findings from the study reveal that 181 (78%) supports the notion that transportation plays a huge role in the reduction of maternal mortality in Calabar; 148 (67%) agreed that good road network has an indirect role in reducing maternal mortality in Calabar; 146 (67%) opined that controlled traffic helps reduced maternal mortality in Calabar; 140 (64%) agreed that emergency vehicles such as ambulances are a good transport medium that reduces maternal death and 159 (71%) agreed that lack of access to transport for women in labour can increase stillbirth and maternal death rates. This study supports Milkowska-Shibata et al (2020). In their study, they identified barriers to accessing healthcare facilities to include transportation, health infrastructure in the rural areas.…”
Section: Hindrances To Access To Hospital Infrastructure In the Provisupporting
confidence: 58%
“…The use of historic comparison, before and after ALSO and BLSO were implemented, is a weakness of this evaluation, as changes in the time frame may have occurred that impact on PPH related maternal mortality and stillbirth, and have not been accounted. Nevertheless, the factors associated with PPH maternal mortality highlight known problems in the area related to access to antenatal care 29 31 , and delivery before or after implementation of the courses remained a significant factor after adjustment for known confounders. Reduction of MMR over time is not smooth or inevitable in this setting.…”
Section: Discussionmentioning
confidence: 94%
“…Home birth (59% of deliveries in our sample) demonstrated the largest (inverse) association with HepB-BD vaccination (aOR 0.32). Achieving high coverage of the HepB-BD vaccine in Myanmar almost certainly will require concerted efforts to redistribute health services, to increase facility deliveries by overcoming barriers to facility delivery [39,40], to increase availability of the HepB-BD at facilities, and also to develop strategies that facilitate timely administration of the HepB-BD to newborns delivered at home [41,43].…”
Section: Discussionmentioning
confidence: 99%